A bioacústica como ferramenta adicional para o estudo da estrutura e dinâmica de uma comunidade de aves em mata estacional semidecidual - Catalano, Ana Luiza Camargo (2020)
Understanding the dynamics and structure of bird communities in forest fragments provide us important data for conservation. The classification of the community regarding trophic categories and strata is one of the most effective methods to access the status of a given area, whereas sensitivity to fragmentations varies among species regarding their foraging habits, foraging area and occupying strata, and these elements could be lost or altered in smaller fragments. Additionally, the acoustic features of a given community associated with ecological data can provide further information. Since birds that sing in the same frequency band undergo acoustic interference when singing in the same temporal interval, the time of singing and vocal characteristics may reflect distribution patterns of species. Furthermore, because generalist species tend to establish in more fragmented areas, the acoustic community of these habitats tends to suffer constant alterations. Thus this study aimed to access the dynamic and distribution of a bird assemblage in a semi-deciduous forest regarding the ecology and vocal characteristics of the species. Data collection occurred during a year through point counts method, and recordings were made for every sample. The presence of sensitive and specialists’ species such as Habia rubica, Pyriglena leucoptera, and Crypturellus undulatus, and the low abundance of generalists’ species such as Tangara sayaca and Tyrannus melancholicus indicated that this area, that was not previously sampled, presents suitable conservation status to harbor these species. With community characterization based on three vocal spectral variables and occupying strata, we verified that species with significant cooccurrence across the point counts, present more dispersed songs and strata. Also, we carried out a case study regarding the occurrence and vocal activity dynamics of two species (Myiothlypis flaveola and Basileuterus culicivorus) that were registered singing shortly after the other. The significant co-occurrence and the strategies to avoid song overlap suggest that the interspecific interaction may benefit at least one of the species. These results demonstrate that the bioacoustics have fundamental importance regarding species distribution in a fragmented area and could be used as an additional tool to assess the structure and status of habitat.